Heterokonts (xanthophyceae and chrysophyceae) in rivers - Necchi, Orlando [UNESP] (Springer Nature, 2016)
The heterokont classes Xanthophyceae and Chrysophyceae are introduced with its key characteristics and typical benthic river genera. Two relatively widespread genera are the xanthophyte siphonous Vaucheria and the filamentous Tribonema. The heterokont classs (Chrysophyceae) genus Hydrurus is also listed, which consists of a branched colony and can be widespread in cold mountain rivers with turbulent waters.
Keywords: Algae; Benthic; Biodiversity; Chrysophyceae; Heterokontophyta; Xanthophyceae; Yellow-green algae